2023
DOI: 10.1177/15459683231172752
|View full text |Cite
|
Sign up to set email alerts
|

Does Exercise Attenuate Disease Progression in People With Parkinson’s Disease? A Systematic Review With Meta-Analyses

Jiecheng A Li,
Marte B. Loevaas,
Catherine Guan
et al.

Abstract: Introduction Exercise has many benefits for people with Parkinson’s disease (PD) and has been suggested to modify PD progression, but robust evidence supporting this is lacking. Objective This systematic review (PROSPERO registration: CRD42020169999) investigated whether exercise may have neuroplastic effects indicative of attenuating PD progression. Methods Six databases were searched for randomized controlled trials (RCTs) that compared the effect of exercise to control (no or sham exercise) or to another fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 89 publications
1
9
0
Order By: Relevance
“…In 2023, Li and colleagues [ 45 ] reported results of their meta-analysis pooling data on the exercise-induced effects on BDNF concentration from five comparisons in four RCTs with 192 participants with PD [ 52 , 53 , 54 , 55 ]. Overall, their meta-analytic procedure led to a statistically significant result of the effects of exercise versus control on BDNF concentration (see Supplementary S1 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2023, Li and colleagues [ 45 ] reported results of their meta-analysis pooling data on the exercise-induced effects on BDNF concentration from five comparisons in four RCTs with 192 participants with PD [ 52 , 53 , 54 , 55 ]. Overall, their meta-analytic procedure led to a statistically significant result of the effects of exercise versus control on BDNF concentration (see Supplementary S1 ).…”
Section: Discussionmentioning
confidence: 99%
“…In 2020, Johansson et al [ 44 ] included three studies without control groups in their meta-analysis of exercise effects on BDNF levels, showing no significant summary effect size. In 2023, Li et al [ 45 ] and Rotondo and colleagues [ 46 ] pooled data on exercise studies, showing positive effects on BDNF levels compared to controls. Due to the conflicting meta-analytic results and the lack of human PD trials detailing mechanisms of exercise on BDNF levels, the purpose of the present systematic review and meta-analysis is to give an updated overview of the mechanisms and effects of exercise therapy on BDNF levels in PD, in order to bring these insights into the clinical context of physical medicine and rehabilitation for people living with PD.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of exercise on these clinical outcomes can be explained by a variety of mechanisms ( Xu et al, 2019 ), including the synthesis of several neurotrophic factors, as reported in a review of animal studies and in a systematic review in patients with PD ( da Silva et al, 2016 ; Li et al, 2023 ). Brain-Derived Neurotrophic Factor (BDNF) protects the brain against destruction of dopaminergic neurons and acts as a growth factor for dopaminergic neurons of the substantia nigra pars compacta ( Hyman et al, 1991 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research, including recent systematic reviews on the effect of exercise on BDNF levels, limited the analysis to controlled trials only ( Hirsch et al, 2018 ; Li et al, 2023 ; Rotondo et al, 2023 ). Randomised trials provide evidence of efficacy of interventions in “ideal” settings, whereas non-randomised studies more accurately reflect usual clinical practice ( Sørensen et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation